Supervision in social work during war: a tool for preventing burnout and promoting professional growth - Shcherbakova, Olga (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2025)
The article examines the phenomenon of supervision in social work in wartime as one of the key mechanisms for supporting social workers, preventing emotional burnout, and developing professional identity. It is emphasized that in the Ukrainian reality of war, social workers operate under a double burden: they not only help war victims, but also experience traumatic experiences themselves, which creates a special need for professional and psychological support. It is noted that the phenomenon of professional powerlessness, manifested in the feeling of inability to change the client’s circumstances, is a systemic problem of social work in crisis conditions. It is revealed that supervision performs three interrelated functions: educational, supportive, and managerial. In wartime, the main function is supportive, which allows social workers to reflect on their own emotional states, restore internal support, and maintain contact with professional meaning. The supervision process creates a safe environment where professionals can talk about fatigue, anxiety, doubt, or disappointment without fear of judgment. This contributes to the stabilization of emotional state, the development of empathy, and the formation of self-support strategies. Special attention is paid to the barriers to the implementation of supervision in Ukraine. These include the formalization of the supervision process, a focus on control rather than support, insufficient training of supervisors, a lack of systematic management support, and the psychological biases of the specialists themselves, who perceive requests for help as a sign of weakness. It is shown that these barriers can only be overcome through the development of a culture of supervision as an ethical norm of professional life, in which care for employees becomes a strategic resource for the stability of the social system. The article emphasizes the importance of forming a mature professional identity of a supervisor based on reflection, ethical sensitivity, and the ability to create an atmosphere of trust and support. The dual dimension of the role of social institution managers, who are both administrators and supervisors, is revealed. The experience of cooperation between V.N. Karazin Kharkiv National University and the Kharkiv Regional Center for Social Services in creating the advanced training program “Supervision in Social Work” is described. This educational initiative contributes to the professionalization of supervisors, the formation of a community of practitioners, and lays the foundation for the institutionalization of supervision at the national level. It is concluded that supervision in wartime is of strategic importance as a tool for preserving human resources, professional motivation, and ethical resilience of social workers.